2014
DOI: 10.1075/tilar.10.09gra
|View full text |Cite
|
Sign up to set email alerts
|

The pragmatics of word learning

Abstract: The reason for the basic role of observations […] (Quine, 1974: 37) Children use and integrate a variety of information when learning novel words. Most strikingly, children are skillful in drawing inferences about speakers' intentions. This chapter reviews the current state of affairs regarding the wide variety of pragmatic information that children employ in word learning. Current debates on whether seemingly pragmatic phenomena in word learning should be explained by simpler processes are addressed thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 110 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…Both verbal and non-verbal communication can involve large quantities of information that have to be both formulated and deciphered with a range of purposes and intentions in mind ( Jones and LeBaron 2002 ). These dimensions of communication have as much to do with the ability to express oneself, both orally and in writing and the mastering of a language (linguistic competences), as with the ability to use this communication system appropriately (pragmatic skills; see Grassmann 2014 ; Matthews 2014 ), and with social skills, based on the knowledge of how to behave in society and on the ability to connect with others, to understand the intentions and perspectives of others ( Tomasello 2005 ).…”
Section: The 4cs Assessment and Support For Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Both verbal and non-verbal communication can involve large quantities of information that have to be both formulated and deciphered with a range of purposes and intentions in mind ( Jones and LeBaron 2002 ). These dimensions of communication have as much to do with the ability to express oneself, both orally and in writing and the mastering of a language (linguistic competences), as with the ability to use this communication system appropriately (pragmatic skills; see Grassmann 2014 ; Matthews 2014 ), and with social skills, based on the knowledge of how to behave in society and on the ability to connect with others, to understand the intentions and perspectives of others ( Tomasello 2005 ).…”
Section: The 4cs Assessment and Support For Developmentmentioning
confidence: 99%
“…This component assesses language comprehension and the appropriate use of vocabulary. Pragmatic skills are captured by the verbal and non-verbal communication components and refer to the efficient use of verbal and body signals in the context of the game to achieve one’s communicative goals ( Grassmann 2014 ; Matthews 2014 ). Finally, the grid also evaluates social skills with its two last components, social interactions and social cognition, which, respectively, refer to the ability to interact with others appropriately—including by complying with the rules of the game—and to the understanding of other people’ mental states ( Tomasello 2005 ).…”
Section: Assessing the 4cs In Informal Educational Contexts: The Exam...mentioning
confidence: 99%
“…At this stage of development, children are practised in establishing and maintaining a joint focus of attention; thus their attention is often less likely to be diverted and they make fewer errors in identifying the object belonging to a word. Children now interpret words in accordance with the joint focus of attention and orientate themselves at the same time to the speaker's cues—for example, direction of gaze, gestures, actions (Grassmann, ). The dialogic reading of picture books has been shown to be a particularly effective method for language acquisition (eg, Hargrave & Sénéchal, ).…”
Section: Learning and Language Acquisition In Early Childhoodmentioning
confidence: 99%
“…Indeed, according to some theories, children acquire word meanings on the basis of the social-referential cues of their communicative partner (Akhtar et al, 1996; Akhtar & Tomasello, 2000; Baldwin & Moses, 2001; Bloom, 2002; Diesendruck et al, 2004) when they make inferences about the intended meaning of the speaker. These cues can include eye-gaze, pointing or iconic gestures, the intonation of the speech, and the context or common ground of the speaker and the listener (Diesendruck, 2007; Grassmann, 2014). Experiments testing such social-pragmatic accounts have showed that children are sensitive both to the identity of the speaker and to the context in which the novel word is used.…”
mentioning
confidence: 99%